Somatic symptoms are sensitive in predicting interstitial cystitis/bladder pain syndrome: A nationwide cohort study. (January 2017) - Chen, I-Chun; Lee, MingHuei; Wu, Shang-Liang; Lin, Hsuan-Hung; Chang, Kun-Min; Lin, HsiuYing
Objectives: Somatic symptoms are somatic complaints accompanied by disproportionate thoughts, feelings, and behaviors related to such symptoms. The study investigated five International Classification of Diseases, Ninth Revision, Clinical Modification diagnoses hallmarked by somatic symptoms. The study hypothesized an increased risk of interstitial cystitis/bladder pain syndrome in patients with somatic symptoms. Methods: The raw data were obtained from a nationwide health insurance reimbursement database over a 12-year period from 2002 to 2013. The study followed a somatic symptoms cohort ( n = 34, 393) and non-somatic symptoms cohort ( n = 637, 999) for interstitial cystitis/bladder pain syndrome. Both cohorts were stratified into three subgroups based on propensity scores calculated by sex, age, and 17 comorbidities of interstitial cystitis/bladder pain syndrome. Results: The incidence density of interstitial cystitis/bladder pain syndrome between the somatic symptoms cohort and non-somatic symptoms cohort was significantly different in the three subgroups (relative ratio [95% confidence interval], 2.14 [1.01, 4.53], 1.52 [1.47, 1.57], and 1.59 [1.28, 1.98], respectively). The adjusted hazard ratio for interstitial cystitis/bladder pain syndrome was significantly greater in the female-dominant and older age subgroups—subgroup 2 and subgroup 3 (adjusted hazard ratios, 1.47 [1.07, 2.01] and 1.72 [1.38, 2.16], respectively). Conclusion: The longitudinal investigation identified a subsequent risk of interstitial cystitis/bladder pain syndrome in patients with somatic symptoms. Somatic symptoms might be linked to biological pathways that might increase the risk of interstitial cystitis/bladder pain syndrome, much like more traditional psychosocial factors.